Diagrid Structural System: Comparative Study to Reduse the Earthquake Forces on High Rise Building: A Comparative Study on the Efficiency and Performance of Diagrid Structural System in Reducing Earthquake Forces on High Rise Buildings (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Generally Lateral load resistance of structure is provided by interior structural system or exterior structural system. Usually shear wall core, braced frame and their combination with frames are interior system, where lateral load is resisted by centrally located elements. While framed tube, braced tube structural system resist lateral loads by elements provided on periphery of structure. Recently diagrid structural system is adopted in tall buildings due to its structural efficiency and flexibility in architectural planning. Diagrid structure consists of inclined columns on the exterior surface of buildings compared to closely space vertical columns in framed tubes.In present work concrete diagrid structure is analysed and compared with convensional concrete building. A regular 4 and 12 storey building with plan size 20m x 20m located in seismic zone III is considered for analysis. All the structural members are design as per IS-800 (2000).STAAD-PRO software is used for the analysis of structural members. All load combinations of seismic forces are considered as per IS-18932002. Comparison of analysis results in terms of mode shape, lateral displacement, storey drift.